Myasthenia gravis during treatment with anti-PD-1 - succesfull treatment using pirydostygminum – case report and literature review - Tywanek, Ewa; Jankowska, Katarzyna; Zwolak, Agnieszka; Zgliczyński, Wojciech; Łuczyk, Robert Jan (Journal of Education, Health and Sport, 2022)
Background: Against limited effectiveness of known oncological treatment such as chemio-and radiotherapy or surgery, new ways of treatment, such as for example immunotherapy has developed. Usage of immune checkpoint inhibitors (ICPIs), resulting in overactivation of immune system, may significantly raise efficacy of oncological treatment, but simultaneously predispose to occurrence various autoimmunological health complications. Adverse actions of the therapy may affect multiple organs and systems, with the presented example of immune-related neurological complication, myasthenia gravis. This relatively rare condition may be severe, life-threatening illness. Case report: We present a case of 66-year-old male patient diagnosted with a large tumor histopathologically assessed as squamous cell carcinoma. Due to ineffectiveness of implemented chemio- and radiotherapy, he was qualified for anti-PD1 immunotherapy with nivolumab. General treatment tolerance was very good with positive antineoplastic effect. Autoimmune hypothyroidism has emerged, therefore levothyroxine therapy has been implemented. After about a year of using immunotherapy, significant weakness and decrease in muscle strength has appeared, subsequently, immunotheraphy-related myasthenia gravis was raised. Improvement in the patient’s condition was achieved after initiating pyridostigmine treatment. Cessation of antineoplastic treatment wasn’t necessary, what is unusual. Conclusions: Undeniably myastenia gravis may determine serious, life-threatening adverse effect of immunotherapy. Usually requires withdrawal of applied antioncological treatment, and should be treated with immunomodulators, immunosuppressants or intravenous immunoglobulins or plasmaphaeresis, however – as we present- in some cases may be properly cured only with pyridostygmine.